2020
DOI: 10.34190/jel.18.5.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Video Discussion Posts on Social Presence and Course Satisfaction

Abstract: Video is a rich medium that conveys more social cues than text. Use of video in an online discussion forum therefore has the potential to increase social presence in online learning environments. This experimental study compared a group using video for a portion of the required discussion posts to a group using only text in an online undergraduate course. While there was a correlation between perceived social presence and satisfaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, these findings do not agree with Ravi et al (2021), who suggested that email is the ideal online tool for communication, or Xiu & Thompson (2020) and Rudi et al (2015), who posited websites as the better choice. One possible reason for the popularity of discussion forums is that files can now be uploaded and downloaded from those platforms, whether on mobile devices or web browsers, making them more accessible compared to websites or emails.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, these findings do not agree with Ravi et al (2021), who suggested that email is the ideal online tool for communication, or Xiu & Thompson (2020) and Rudi et al (2015), who posited websites as the better choice. One possible reason for the popularity of discussion forums is that files can now be uploaded and downloaded from those platforms, whether on mobile devices or web browsers, making them more accessible compared to websites or emails.…”
Section: Discussionmentioning
confidence: 68%
“…These study items have been insisting on enhancing overall family educational culture, so the choice of the discussion forum was not new, since it conforms with many studies (Blau and Hameiri, 2017;Hammersley et al, 2020;Dolan, 2022;Xiu & Thompson, 2020) suggested that families of all types tend to opt for choices that offer easy two-way communication synchronously or asynchronously, with all information and resources available for all participants/parents in one platform. This approach also conforms with Dolan (2022) and Hammersley et al (2020) findings of the discussion forum as the ideal choice for parents when it comes to enhancing student achievement by facilitating discussions of student educational challenges and needs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Depending on the knowledge area, strategy, and teaching objectives, demonstrations, interactive cases, online notes, animations, simulations, exams, games, and questions may be included [9]. For example, as an online educational resource, video can help to promote social connection as well as develop technical and communication skills [10]. In turn, activities or practical exercises should not be ignored in online learning and may include problems or questions [11].…”
Section: Introductionmentioning
confidence: 99%